Daśanāmī samādhis in West Bengal: Preliminary Observations. (13th June 2021) - Hatcher, Brian A
Abstract: This essay provides a summary of research on the history and material legacy of a Daśanāmī monastic network established in modern Bengal. Centred on the pilgrimage centre of Tārakeśvar, at its peak this network area covered much of southwestern Bengal, integrating disparate temples and economic centres. The essay calls special attention to the role of samādhis (burial monuments) in anchoring Daśanāmī monasteries ( maṭhas ) in the local landscape and also illustrates the challenge of documenting sites when these material markers have deteriorated, vanished, or been renovated.